Dual-Axial Tool Servo Diamond Turning of Hierarchical Micro-Nano-Structured Surfaces - Xiaonan Pu; Zihui Zhu; Li Chen; Peng Huang; Yulin Wang; Zhiwei Zhu (Journal of Manufacturing and Materials Processing, 2021)
This paper reports on a dual-axial tool servo diamond turning method for the one-step fabrication of hierarchical micro-nano-structured surfaces. With respect to the dual-axial servo motion (XZ), the z-axis motion can generate the primary surface with a complex shape, and the x-axis motion is used to synchronously form the secondary structure via controlling the residual tool marks. The toolpath determination algorithm for the developed turning method is described in detail, and the effect of the machining parameters on the basic feature and sizes of the generated secondary structures is investigated through conducting the numerical simulation for both toolpath and surface generation. The simulation result indicates that the additional x-axial motion is effective for the deterministic generation of a variety of secondary structures. Finally, taking advantage of an ultra-precision lathe with a self-developed tri-axial FTS, a hierarchical surface with high accuracy is practically generated.